Analisis Prototype Pengering Gambir Dengan Memanfaatkan Energi Surya - Safril Safril; Ichlas Nur (Jurnal Teknik Mesin, 2004)
Indonesia is one of the countries which has high intensity solar radiation. This is very useful in term to exploite solar radiation for drying gambir processes. In Indonesia many people in west Sumatra worked gambir. More than 80 % produce gambir in Indonesia came from west Sumatra. In generally gambir can produce from until 1,5 year old depend on grow up level. Harvest can do it cutting branch-branch and leave (not more old and not more young) with knife or to harvest cut longer is 40-60 cm from beginner, it means new sprout should be in arm-pit branch can good grow up. Cutting and to harvest leave must do it in the morning 8.00 until 12.00, if can get soft atmosphere can enough to harvest branch all leave after 12.00 that can produce and qualities of gambir is low continued step is to boiled leave, to press leave, to sediment sticky plant-sap, to sifting plant-sap, to printed matter and to dry.